Variability in trunk segmentation in the centipede order Scolopendromorpha: a remarkable new species of Scolopendropsis Brandt (Chilopoda: Scolopendridae) from Brazil - Chagas-Junior, Amazonas; Edgecombe, Gregory D.; Minelli, Alessandro (Zootaxa, 2008)
Of the two centipede orders that complete segmentation during embryogenesis, most species belonging to Geophilomorpha have an intraspecifically variable number of trunk segments, whereas those of the Scolopendromorpha have been assumed to have a fixed segment number, with minor variation (21 or 23 segments) across the group as a whole. Trunk segment numbers are used as a taxonomic character as high as the familial or subordinal level in Scolopendromorpha. The first known instance of variability in trunk segment numbers within a scolopendromorph species has recently been proposed for the Brazilian Scolopendropsis bahiensis (Brandt, 1841), which has either 21 or 23 segments in different parts of its geographic range. Here we document a closely related scolopendrid from Tocantins State, central Brazil, Scolopendropsis duplicata n. sp., which differs from S. bahiensis in having either 39 or 43 segments. This unique segment count is incorporated into a revised diagnosis of the order Scolopendromorpha. The deeply nested position of Scolopendropsis within the Scolopendridae implies that the geophilomorph-like trunk segment number in S. duplicata is convergent with similar segmentation in Geophilomorpha.